Exploring Constructivism in the Context of English Material Development for Senior High Schools: A Literature Review Approach - Nuraini, Hery; Gailea, Nurhaedah; Samanhudi, Udi (Journal of English Education and Teaching, 2025)
English language learning in high schools in Indonesia still focuses on theory, namely memorizing tenses, practicing grammar, and sentence structure, while communicative skills such as spontaneous speaking and real-life interactions receive very little attention. Previous research shows that students feel low on confidence and limited facilities and practice time. Psychological aspects such as self-confidence, student learning styles, technology integration, and authentic assessment are still rarely an integral part of teaching material design. This study aims to map best practices and weaknesses in the development of constructivist-based English teaching materials in high schools, with an integrative focus on the use of technology, variations in student learning styles, and authentic assessment, so that students' communication skills and confidence are improved. The method used is a literature review from 2018-2024 from national and international journals, proceedings, and research reports. This study uses thematic analysis techniques and framework analysis. The main findings indicate that approaches such as PjBL and CTL that involve projects, simulations, discussions, and real-life interactions can increase student engagement, creativity, critical thinking, and self-confidence. The integration of technology as a learning medium is indeed appealing, but its implementation has not been optimal in supporting authentic communication. Diversity in learning styles strengthens the effectiveness of teaching materials, and authentic assessments help measure students' actual abilities. This study fills a gap in the local literature by combining aspects of technology, learning styles, and authentic assessment within a single framework.